The Baku period in the activity of Levon Mirzoyan, the first head of the Kazakh SSR - Victor Z., Akopyan (Kavkazologiya, 2022)
This article is devoted to the famous political and party figure LevonIsaevich Mirzoyan, who held high public positions in several regions of the USSR, particularly in the Azerbaijan SSR; the Ka-zakh ASSR transformed into a union republic under his leadership, the successor of which is the modern Republic of Kazakhstan. In recent years, under the influence of biased politicians and his-torians, the activities of a well-known politicians, thanks to whom an incredible civilizational leap of the people, who had previously wandered through the boundless Asian expanses for thousands of years, have been falsified and his services to Kazakhstan and its people have been forgotten. Other people’s atrocities are attributed to him, against which he fought. Of course, the activities of the Republican leadership in the late 30s were not without the stamp of the brutal Stalinist era of the Great Turning Point.